Adherence and biofilm formation of non-Candida albicans Candida species - Silva, Sónia Carina (2011)
Most cases of candidosis have been attributed to Candida albicans, but recently non-Candida albicans Candida species have been identified as frequent human pathogens. Candida pathogenicity has been attributed to several factors, including adhesion to medical devices and/or host cells, biofilm formation, and secretion of hydrolytic enzymes (proteases, phospholipases, and haemolysins). Although ‘new’ Candida species are emerging, there is still a lack of information about their pathogenicity. This review discusses recent advances in our knowledge of C. glabrata, C. parapsilosis, and C. tropicalis virulence factors, specifically those of adhesion and biofilm formation, which are key components in Candida pathogenicity.